Erratum: Employability of Egyptian Agriculture University Graduates: Skills Gaps - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Ebner, P., Thompson, L., Ghimire, R., Dissanayake, D. G., Joshi, N., & Saleh, W. D. (2020). Employability of Egyptian Agriculture University Graduates: Skills Gaps. Journal of International Agricultural and Extension Education, 27(4), 128-143.” was incorrect as published. The correct DOI is: 10.5191//jiaee.2020.274128